2014
DOI: 10.1371/journal.pone.0088263
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Posttraumatic Stress Disorder Symptoms and Its Relationship with Coping Skill and Locus of Control in Adolescents after an Earthquake in China

Abstract: Background/ObjectivesPost-traumatic stress disorder is a common psychological maladaptation among adolescents after undergoing an earthquake. Knowledge about the prevalence and maintenance of post-traumatic stress disorder symptoms and the changes of its predictors over time can help medical providers assist adolescent survivors with mitigating long-term impacts. This study examined the changes in posttraumatic stress disorder symptoms and its relationship with coping skill and locus of control among adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 31 publications
11
59
1
1
Order By: Relevance
“…Studies generally report better outcomes in individuals classified as being more internal than external, concluding that it is psychologically healthy to perceive that one has control over those things which one is capable of influencing. LoC is not static; studies have shown that it is malleable in response to both life events (such as trauma [13,14]) and interventions such as cognitive training [1517], thus suggesting that it is possible to improve a person’s ability to internalise, which may incur later health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Studies generally report better outcomes in individuals classified as being more internal than external, concluding that it is psychologically healthy to perceive that one has control over those things which one is capable of influencing. LoC is not static; studies have shown that it is malleable in response to both life events (such as trauma [13,14]) and interventions such as cognitive training [1517], thus suggesting that it is possible to improve a person’s ability to internalise, which may incur later health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The version of the internal/external LOC scale used in this study has acceptable reliability (=0.71). 11 The data gathered was entered using Microsoft Excel and then exported to SPSS for analysis. The quantitative variables, such as age, will be presented as Mean+SD.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that external LOC is related to a higher level of PTSD-symptoms. 11,12 Rotter (1966) explained that an internal LOC protects an individual from PTSD, while an external LOC develops PTSD after stressful life events. 10 However, seeking psychological assistance is not typically done, possibly due to the existing socio-cultural barriers and stigma, or due to the lack of awareness of the nature of MVA-associated stress and LOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The Impact of Event Scale-Revised (IES-R) is used to measure PTSD symptoms (Weis & Marmar, 1997, Lithuanian version Kazlauskas…”
Section: įTeikta 2015 07 18mentioning
confidence: 99%